Pengaruh Video Pencegahan Gastritis (Petis) Terhadap Pengetahuan dan Sikap Remaja di SMA Negeri 11 Luwu - Haya Saputri; Dian Furqani Hamdan (Indonesian Journal of Science and Public Health, 2025)
Gastritis is an acute, chronic inflammation of the gastric mucosa. This research was conducted because there is survey data from the Luwu District Health Office in 2023 explaining that gastritis ranks second among the top 10 most common diseases, and the working area of the Lamasi health center is also one of the areas with gastritis cases. Data from Puskesmas Lamasi from January to December 2023 shows that the age group most affected by gastritis is adolescents aged 15-19 years. The lack of knowledge among teenagers about gastritis and the mistakes in their eating habits have become a common practice that can lead to gastritis. Therefore, an intervention is needed to prevent this, such as providing education, one of which is using a gastritis prevention video (petis). Objective: This study aims to determine the effect of gastritis prevention videos (petis) on the knowledge and attitudes of adolescents at SMA Negeri 11 Luwu in 2024. Method: This research is a quantitative study with a pre-experimental approach using a One Group Pretest-Posttest design. The population in this study consists of all the teenage students at SMA Negeri 11 Luwu in 2024, totaling 1,015 respondents. The sampling in this study used the Slovin formula and cluster random sampling technique, resulting in a sample size of 89 respondents. Data collection used an instrument in the form of a questionnaire. The collected data is then processed and analyzed using a statistical program (SPSS). Data analysis includes univariate analysis to determine frequency distribution and bivariate analysis using the Wilcoxon Signed Ranks Test. Results: The study shows that there is an influence between the gastritis prevention video (petis) on respondents' knowledge with a value